Information technologies and the development of professional knowledge and identity in teacher education - Ponte, João Pedro da (2011)
This paper addresses the preparation in ICT of preservice mathematics teachers. We describe the aims, assumptions, and work carried out in a course offered at the University of Lisbon and briefly discuss the processes involved in the development of professional knowledge and the formation of professional identities. Using a qualitative methodology, based on the administration of free-response questionnaires to the student teachers enrolled in the course in 1999-2000, we analyze their general perspectives about ICT, the implications of the use of ICT in their view of teaching methodologies, and their development of a professional identity. This work provides suggestions for teacher education practice and for further research.